“The Heart of the Collective”: Black Left Feminism, Black Women’s Intellectual History and Freedomways Magazine, 1930-1985 - Eglen, Lauren (2022)
This thesis is the first to explore Freedomways: A Quarterly Review of the Freedom Movement through the lens of its women editors, as a Black feminist intellectual project that expands understanding of Black intellectual history and Black feminism. As activist-intellectuals, Esther Cooper Jackson, Shirley Graham Du Bois, Jean Carey Bond, and other women in the Freedomways collective shaped the magazine’s content and editorial outlook in line with their established political viewpoints, and from their distinct intellectual approaches. The magazine was the way that these women sustained their Black Left feminist politics that they had developed in the 1930s and 1940s Popular Front period, crafting it as a platform for leftist women’s ideas and analyses of the global freedom struggle that could influence a new generation of feminist activists and writers with whom they built inter-generational relationships.